Πτυχές του υλικού εξ αποστάσεως εκπαίδευσης με έμφαση στους πόρους ταινιών - Maniatis, Antoine (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The current study focuses on various actual aspects of didactic material, which could be used in the framework of open and distance education, emphasizing film resources and more generally images. On the one hand, Internet, mainly Youtube, has well promoted video as a means of expression, video managed to promote various fundamental rights, such as the rights to recreation, research and education. Documentaries constitute an important tool in the educational proceeding whilst didactisation constitutes a wider proceeding, related to teaching procedures which introduce documents coming from various sources. On the other hand, a branch of law has emerged in the digital era, consisting in personal data law. At least in France, the right to image is an autonomous right in comparison with the right to privacy, in spite of the fact that its explicit consecration in Civil Code has been removed. The current research is completed by an approach relevant to the creation of alternative teaching material on open and distance learning, including inter alia a didactic documentary.